2-Dodecyl-6-methoxycyclohexa-2,5-dien-1,4-dione alleviates liver fibrosis and improves intestinal flora and bile acid metabolism - He, Yongfei; Hoa Pham, Thi Thai; Xu, Junming; Hong, Shengjie; Wang, Jicai; Zhai, Hang; Tao, Qiang; Li, Ruixi; Zhang, Guangquan; Shi, Xianjie (Frontiers in Pharmacology, 2025)
BackgroundThe bioactive compound 2-Dodecyl-6-methoxycyclohexa-2,5-diene-1,4-dione (DMDD), derived from the horn root of star fruit, exhibits therapeutic promise through its modulation of the TGF-β1 pathway and regulation of bile acids.MethodsIn this study, a liver fibrosis model was established in Kunming mice (KM) induced by carbon tetrachloride (CCL4), and DMDD (50 mg/kg) was administered intragastrically. HE staining, Masson staining, and Sirius staining were used to evaluate the effect of DMDD on liver fibrosis. The Illumina sequencing platform was used to detect intestinal flora and liver transcriptome information in mouse feces, and high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) technology was used to detect bile acid content changes in mouse feces.ResultsThe results show that DMDD can mitigate liver fibrosis-induced damage in mice, potentially through the suppression of the TGF-β/Smad signaling pathway. Furthermore, DMDD increased the abundance of Lactobacillus, Bacteroides, Ruminococcaceae, Ruminococcus, and Oscillospira, thereby addressing intestinal flora disturbances and regulating bile acid metabolism.ConclusionOur study suggests that DMDD alleviates liver fibrosis by inhibiting the TGF-β/Smad signaling pathway, restoring gut microbiota homeostasis, and balancing bile acid metabolism.